Diagnosis and management of congenital chylothorax - Valentin Varlas; Vlad Dima; Roxana Georgiana Bors (Amaltea Medical Publishing House, 2022)
Congenital chylothorax, the accumulation of lymph in the pleural space, is a rare and serious condition that can appear alone or accompany congenital anomalies. Ultrasonography and pleural fluid analysis can diagnose it early from the fetal period. Both prenatal and postnatal therapeutic interventions improve the fetal prognosis and decrease the rate of complications.